Siam : - Thompson, P. A. (J. B. Millet Co., 1910)
This book introduce about Bangkok, present conditions, the Buddhist religion, temples, images, and symbols. The brotherhood of the yellow robe, the pees and charms, Siamese art, rice and fish...